Response Monitoring Theta-Band Activities Across Emotional Contexts in Schizophrenia and Bipolar Spectrum Disorders - Takakuni Suzuki; Margo W. Menkes; Melvin G. McInnis; Jian Kang; Tara A. Niendam; Maureen A. Walton; Patricia J. Deldin; Ivy F. Tso; Stephan F. Taylor (Biological Psychiatry Global Open Science, 2025)
Background: Schizophrenia spectrum disorder (SZ) and bipolar spectrum disorder (BD) have traditionally been treated as different conditions but share many characteristics, including cognitive control deficits. Electroencephalogram (EEG) indicators of response monitoring, including error-related negativity (ERN) and theta-band activities (4–8 Hz), have been proposed as transdiagnostic indicators of cognitive control. Research has found that the ERN and theta power are blunted in SZ, but findings have been less consistent in BD. Individuals with SZ and BD also show difficulty in emotional contexts. However, no research has investigated response-monitoring theta activities in SZ and BD concurrently or in emotional contexts. Methods: Data were collected from 32 participants with SZ, 33 participants with BD, and 33 healthy control (HC) participants. EEG was recorded while participants completed 3 modified flanker tasks using arrow, unpleasant, and pleasant stimuli. Effects of group and task on postresponse event-related potentials (ERN, correct-related negativity), theta total power, and theta intertrial phase coherence (ITPC) were investigated using mixed analysis of covariance, controlling for age and accuracy. Results: The SZ group did not show the ERN modulation by task that was found in the HC and BD groups. The SZ group showed attenuated theta power across all tasks, and the BD group showed attenuated power only on error trials with unpleasant stimuli. Both SZ and BD groups showed emotional modulation for theta ITPC. Theta power was correlated across tasks, suggesting that it is task invariant, while ITPC was not, suggesting that it is task-specific. Conclusions: SZ and BD show different effects of emotional stimuli on cognitive control. To elucidate similarities and differences, concurrent data collection from individuals with SZ and BD across contexts is needed.